PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DENGAN KOMITMEN ORGANISASI SEBAGAI INTERVENING - ., Nuryani (STIE AUB Surakarta, 2014)
The purpose of this study is to investigate the influence of leadership, Organization culture and Organization commitment to teachers performance of the Government Vocational High School 4 at Klaten. The Hypothesizing which have been formulated in this research are: there is direct and indirect influence of leadership, Organization culture across Organization commitment to teachers performance of the Government Vocational High School 4 at Klaten. The research is a survey to teachers performance the Government Vocational High School 4 at Klaten with 70 respondents Data have been collected with questionnaires processed with, validity and reliability test, the path analysis, t test, F test and test of R2 . The t test result shows that there is influence of leadership, Organization culture and Organization commitment to teachers performance of the Government Vocational High School 4 at Klaten. The F test result shows that there is influence of leadership, Organization culture and Organization commitment to teachers performance of the Government Vocational High School 4 at Klaten simultaneously. From path analysis shows that leadership has a bigger influence to performance than across Organization commitment, and Organization culture as well. It means that Organization commitment canât be as an intervening variable because the coefficient is as smaller than coefficient as direct influence. From test of R2 shows the independent variable can explain performance about 86,4% and 13,6% can been explained by another variable: commitment, ability. Keyword: leadership, Organization culture, Organization commitment, performance